Design of a Web Server Based Monitoring System for Aviation Security Equipment Maintenance with an Interactive Dashboard and Telegram Notification Integration at UPBU Silampari - Emmalitna Caroline Sembiring; Eriyandi Eriyandi; Febria Roza (Lembaga Pengembangan Kinerja Dosen, 2026)
The Silampari Airport Operating Unit (UPBU Silampari) is a Class III airport under the Directorate General of Civil Aviation that plays a strategic Role in the South Sumatra region. In its operations, maintenance activities for aviation security equipment such as the X-Ray Baggage Scanner, Walk Through Metal Detector (WTMD), Hand Held Metal Detector (HHMD), and CCTV are still conducted manually using paper-based forms. This process poses several challenges, including the risk of data loss, delays in inspections, and difficulties in retrieving historical maintenance records, particularly due to the limited number of airport electronic technicians. This study aims to design and develop a web server–based monitoring system for the maintenance of aviation security equipment, equipped with an interactive dashboard and Telegram notification integration. The system is designed to support routine maintenance monitoring that is digitally documented, structured, and in accordance with Directorate General Decree KP 241 of 2014 and the principles of electronic government efficiency as stated in Presidential Instruction No. 1 of 2025. The research employs the Waterfall Software development model, which includes stages of requirements analysis, system design using Unified Modeling Language (UML), Implementation with PHP, MySQL, HTML, and CSS, and testing using the Black Box Testing method. The resulting system design is expected to facilitate technicians in recording, storing, and monitoring equipment conditions in real-time while improving the efficiency and accuracy of maintenance activities at UPBU Silampari.